Pemahaman Guru dalam Penskoran Tes Bentuk Pilihan Ganda dan Uraian pada Pembelajaran PAI di MTsS Azzanjabil Bireuen - Asraddin, Asraddin (Pase: Journal of Contemporary Islamic Education, 2024)
In the context of Islamic Religious Education (IRE), accurate scoring techniques not only reflect students’ cognitive achievement but also support character development and the internalization of spiritual values. This study aims to explore in depth the understanding of IRE teachers regarding scoring techniques for multiple-choice and essay-type tests, as well as their implications for the learning process at MTsS Azzanjabil in Bireuen District. The research employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. Data analysis follows the model of Miles, Huberman & Saldaña (2014), which includes data condensation, data display, and conclusion drawing/verification. The findings reveal that teachers still rely on conventional scoring methods for multiple-choice tests, assigning fixed scores without weighting or correction for guessing. In contrast, for essay-type tests, teachers demonstrate a more nuanced understanding by considering the difficulty level of questions and the quality of student responses. The scoring practices have shown a positive impact on students’ learning motivation, although they are not yet fully supported by standardized scoring guidelines or rubrics. Teachers’ understanding of scoring techniques has significant implications for the quality of evaluation and the overall learning process in IRE. Strengthening teacher competence through training and the development of structured scoring guidelines is essential to ensure that assessments are conducted more objectively, proportionally, and in alignment with the values of Islamic education.